Angiotensin II stimulates both Na(+)-H+ exchange and Na+/HCO3- cotransport in the rabbit proximal tubule. - Geibel, J (1990)
Angiotensin II (AII) is a potent stimulus for HCO3- reabsorption in the rat proximal tubule in vivo. To determine the ionic mechanism of increased HCO3- reabsorption, we have examined the effect of AII on luminal Na(+)-H+ exchange and basolateral Na+/HCO3- cotransport in perfused S1 proximal tubules isolated from superficial nephrons of the rabbit kidney. Transporter activity was assessed by removing Na+ from both luminal and basolateral (i.e., bath) solutions and determining the rate at which intracellular pH (pHi) increased after Na+ was returned to only the lumen or only the bath. pHi was measured with the pH-sensitive fluorescent dye 2', 7'-bis(2-carboxyethyl)-5(and 6)-carboxyfluorescein. We found that basolateral administration of 1 nM AII not only increased the rate of luminal Na(+)-H+ exchange approximately 3.5-fold but also increased the rate of basolateral Na+/HCO3- cotransport approximately 2.5-fold. 5-(N-Ethyl-N-isopropyl)amiloride (50 microM) blocked luminal Na(+)-H+ exchange before and after stimulation by AII but had no effect on basolateral Na+/HCO3- cotransport. Conversely, 4,4'-diisothiocyanato-2,2'-stilbenedisulfonate (50 microM) blocked basolateral Na+/HCO3- cotransport before and after AII but had no effect on luminal Na(+)-H+ exchange. Our data thus indicate that, at least under the conditions of our assay, AII independently stimulates the transporters responsible for both the luminal and basolateral steps of transepithelial HCO3- reabsorption.